HOW ESSENTIAL IS THE PROTECTING MANTRA IN THE PERFORMING ARTS IN THE SOUTH COASTAL COMMUNITY? (Seberapa Penting Mantra Pelindung dalam Seni Pertunjukan di Masyarakat Pesisir Selatan?) - Irdawati Irdawati; Emridawati Emridawati; Ibnu Sina; Yon Hendri; Delfi Enida (SAWERIGADING, 2023)
This research highlights the function of an antidote or protector for the Pesisir Selatan populace during performance art. Based on prior research findings, it determines that spells possess a structure and function that serves as an antidote. At the same time, mantras contain cultural and religious values. The mantras recited by Minang shamans in their native language are based on verses from the Qur'an and employ the words of Allah SWT and Prophet Muhammad SAW. These mantras serve as a means of expressing belief while maintaining the unity and divinity of Allah SWT. A soft tone characterizes the recitation and employs ideational language to convey ideas and thoughts, reflecting the supernatural powers of the sources and containing hopes and requests. The present study employs a descriptive methodology with a phenomenological orientation, explicitly examining the phenomenon of utilizing mantras to counter adverse effects within a given community. The research involves an analysis of the structure and contextual presentation of mantras as observed within the Minang community. Furthermore, the study involved interviews with informants who served as experts in mantras, providing descriptions of factual or empirical linguistic phenomena present in individuals' daily experiences. The study's findings, which involved interviews with multiple informants, indicate that chants believe to possess magical properties, specifically the ability to avert a negative outcome. AbstrakPenelitian ini mengkaji tentang fungsi penawar atau pelindung bagi masyarakat Pesisir Selatan pada seni pertunjukan. Berdasarkan temuan penelitian sebelumnya, telah ditetapkan bahwa mantra memiliki struktur dan fungsi yang berfungsi sebagai penawar racun. Pada saat yang sama, mantra mengandung nilai-nilai budaya dan agama. Mantra yang dibacakan oleh dukun Minang dalam bahasa asli mereka didasarkan pada ayat-ayat Al-Qur'an dan menggunakan kata-kata Allah SWT dan Nabi Muhammad SAW. Mantra-mantra tersebut berfungsi sebagai sarana mengungkapkan keyakinan dengan tetap menjaga keesaan dan ketuhanan Allah SWT. Nada lembut mencirikan pembacaan dan menggunakan bahasa ideasional untuk menyampaikan ide dan pikiran, mencerminkan kekuatan supranatural dari sumber dan mengandung harapan dan permintaan. Penelitian ini menggunakan metodologi deskriptif dengan orientasi fenomenologis, khususnya mengkaji fenomena penggunaan mantra untuk melawan efek negatif dalam suatu komunitas tertentu dalam seni pertunjukan. Penelitian ini melibatkan analisis struktur dan kontekstual penyajian mantra-mantra yang diamati dalam masyarakat Minang di Pesisir Selatan. Selain itu, penelitian ini melibatkan wawancara dengan informan yang berperan sebagai ahli mantra, memberikan deskripsi fenomena linguistik faktual atau empiris yang hadir dalam pengalaman sehari-hari individu. Temuan penelitian, yang melibatkan wawancara dengan banyak informan, menunjukkan bahwa nyanyian diyakini memiliki sifat magis, khususnya kemampuan untuk mencegah hasil negatif.